Effect of avian-human joint attention on allospecific vocal learning by grey parrots (Psittacus erithacus) - Pepperberg, I M; McLaughlin, M A (Journal of comparative psychology (1983), 1996)
The authors studied whether grey parrots (Psittacus erithacus) would learn referential English vocalizations if training lacked full social interaction with humans. In previous studies, grey parrots learned human vocalizations most readily when training simultaneously demonstrated the meaning (full reference) and function (full contextual applicability) of the utterance and actively engaged the subject in learning (full interaction). Those studies, however, did not contrast effects of limited and full interaction or examine how interaction affects contextual applicability. Because an important factor in child language acquisition is joint attention-the social interaction between caretaker and human infant concerning objects and actions in their environment-the authors contrasted training in which joint attention was present or absent (i.e., full vs. limited interaction) and found that 2 parrots did not learn in the absence of joint attention but did learn English labels when full interaction was present.